MENINGKATNYA KESADARAN MASYARAKAT TERHADAP KEBAKARAN HUTAN DAN LAHAN GAMBUT SETIAP TAHUNNYA - Mutia Evi Kristhy; Arif Lukman Hakim; Erwin Widyawan; Cindy Claudia; Martha Renatha Limbong; Wismiati Sarvon; Lianata Lianata; Arianto Kapitan Laut; Disa Disa; Astuti Telaumbanua; Ahmad Fadilah Akbar; Gomgom Aldian; Jhosua Kristian Maranatha; Sri Wahyuni; Mariani Mariani; Wantoni Mahendra (Jurnal Pengabdian Kepada Masyarakat Media Ganesha, 2021)
Forest and land fires are natural disasters that greatly damage ecosystems, and Indonesia is no exception, where Indonesia is an archipelagic country that has a lot of forest and peatland areas. Almost every year forest and land fires occur when entering the dry season, especially in the province of Central Kalimantan which has the characteristics of peat soil. One of the efforts to prevent and control forest and land fires is to conduct reforestation. As a form of community service, the author in the KKN (Real Work Course) activity carried out one of the work programs related to the socialization of forest and peatland fires. The writing of this article focuses on efforts to increase public awareness of the risk of forest and land fires with poster media through WhatsApp groups, Instagram, and YouTube. The method used is descriptive method. Therefore it is very important to raise awareness for the community, both from among children, adolescents, adults, and parents. If this is not done, sooner or later it will have an impact on various sectors, both the environment, food security, economic growth will experience a slowdown, and people will experience loss of income. With socialization through WhatsApp groups, Instagram, and YouTube media, people can have a new level of awareness and insight on the importance of protecting forests and land.